The Effect of Resitasi Method on Physics Learning Outcomes of Grade XI Students of SMAN Pemana, Sikka Regency (Jurnal Pendidikan Fisika, 2019)
Resitasi method is a method of teaching that enable learners to perform the tasks assigned by the teacher after explaining the topic. The tasks referred to here is solving problems that prepared by the teacher and will be distributed to each learner. This research is experimental research design used randomized posttest-only control group design, in order to compare the results of experimental physics learning between classes taught using the control class resitasi method taught using conventional methods. Number of students in the experimental class and control class that equal numbers of each class consists of 28 people. Through testing shows that the normality of the population come from a normally distributed population and the variance is homogeneous. In the descriptive analysis of learning outcomes visible difference in scores between grade physics experiment and control class that is 18.82 with a standard deviation of 5.02 in the experimental class while the control class of 16.14 with a standard deviation of 5.03. From the results of hypothesis testing shows that there are differences in learning outcomes among learners experimental class and control class using sigifikansi level α = 0.05. It can be concluded that learning by using the method of recitation is more influential than the learning using conventional methods in achieving the goals of learning physics.Keywords: Resitasi, Learning Outcomes, Experimental Class, Control Class, Learning PhysicsMetode resitasi merupakan metode pengajaran yang mengaktifkan peserta didik untuk mengerjakan tugas-tugas yang diberikan oleh guru setelah menjelaskan suatu materi. Tugas-tugas yang dimaksud disini adalah menyelesaikan soal-soal yang telah disusun oleh guru dan akan dibagikan kepada setiap peserta didik. Penelitian ini merupakan penelitian eksperimen dengan desain penelitian yang digunakan adalah Randomized posttest-only control group design, yang bertujuan untuk membandingkan hasil belajar fisika antara kelas eksperimen yang diajar dengan menggunakan metode resitasi dengan kelas kontrol yang diajar dengan menggunakan metode konvensional. Jumlah peserta didik pada kelas eksperimen maupun kelas kontrol sama jumlahnya yaitu masing-masing kelas terdiri dari 28 orang. Melalui pengujian normalitas terlihat bahwa populasi berasal dari populasi  yang terdistribusi normal dan varians yang homogen. Pada analisis deksriptif terlihat perbedaan skor hasil belajar fisika antara kelas eksperimen dan kelas kontrol yaitu 18,82 dengan standar deviasi 5,02 pada kelas eksperimen sedangkan pada kelas kontrol 16,14 dengan standar deviasi 5,03. Dari hasil uji hipotesis terlihat bahwa terdapat perbedaan hasil belajar antara peserta didik kelas eksperimen dan kelas kontrol dengan menggunakan taraf sigifikansi α = 0,05. Sehingga dapat disimpulkan bahwa pembelajaran dengan menggunakan metode resitasi lebih berpengaruh jika dibandingkan dengan pembelajaran yang menggunakan metode konvensional dalam mencapai tujuan pembelajaran fisika.Kata kunci: Resitasi, Hasil Belajar Fisika, Kelas Eksperimen, Kelas Kontrol